Lack of GPR88 enhances medium spiny neuron activity and alters motor- and cue-dependent behaviors - Quintana, Albert (2012)
The striatum regulates motor control, reward, and learning. Abnormal function of striatal GABAergic medium spiny neurons (MSNs) is believed to contribute to the deficits in these processes that are observed in many neuropsychiatric diseases. The orphan G-protein-coupled receptor (GPCR) GPR88 is robustly expressed in MSNs and regulated by neuropharmacological drugs, but its contribution to MSN physiology and behavior is unclear. Here we show that in the absence of GPR88, MSNs have increased glutamatergic excitation and reduced GABAergic inhibition that together promote enhanced firing rates in vivo, resulting in hyperactivity, poor motor-coordination, and impaired cue-based learning in mice. Targeted viral expression of GPR88 in MSNs rescues the molecular and electrophysiological properties and normalizes behavior, suggesting that aberrant MSN activation in the absence of GPR88 underlies behavioral deficits and its dysfunction may contribute to behaviors observed in neuropsychiatric disease.